PENGARUH PENGELUARAN PEMERINTAH SEKTOR KESEHATAN, PENDIDIKAN, DAN INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI ACEH - Safitri, Intan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study ains to analyze the effect of government spending on the Human Development Index. Government spending on health, education, and infrastructure are used as the independent variables and the Human Development Index as the dependent variable. The data used is data panel from 23 districts / cities in Aceh in period 2008-2014. Panel data method of Random Effect Model is uses in analysis. The results showed that government spending sectors of health, education and infrastructure hasÂ  positive on the Human Development Index but significance different level. Only spending on health sector is significant, while spending on education and infrastructure are not sigificant. Then, government policy on spending is expected to beeffective to encourage the HDI. Cities governments are expected to conduct of policies so that government spending can be significant to the Human Development Index by spending evenly.Keywords: Government Spending of Health, Government Spending of Education, Government Spending of Infrastructure, The Human Development Index (HDI)